Oxytocin administration to clinicians in acute psychiatric care settings: a feasibility study - Nir, Ayelet; Sedoff, Omer; Yenon, Gal; Hirsch Klein, Efrat; Schreibman, Yaen; Qashu, Khalil; Maoz, Hagai; Bloch, Yuval; Tzur Bitan, Dana (Frontiers in Psychiatry, 2025)
IntroductionOxytocin (OT) has been previously found to facilitate therapeutic outcomes when administered to patients. Recent evidence suggests that therapist’s OT levels similarly influence clinicians’ ability to respond to patients in an empathic and responsive manner. However, no study previously assessed the impact of OT administration to clinicians treating patients in acute settings. This preliminary feasibility study investigated the applicability and trends of effects of OT administration to clinicians performing triage assessment in a public psychiatric emergency room, while focusing on perceived empathy and quality of the therapeutic encounter.MethodsThree clinicians were double-blindingly administered with intranasal OT at one day, and saline placebo (PLC) at a different day. The patients they met (N = 16) provided self-reports on the clinician’s empathy (BLRI), the quality of the session (SEQ), and their level of psychological distress (HSCL-11). The Wilcoxon signed-rank test was used to compare ratings across the two conditions.ResultsPatients reported significantly deeper and more valuable meeting with the clinicians following OT administration to clinicians (S = 32.0, p = 0.0398) as well as significantly lower levels of distress (S = 70.5, p = 0.0343). Clinicians perceived empathy was higher after OT administration compared to PLC, however, this difference did not reach statistical significance (S= 38, p = 0.1675).ConclusionAlthough these results should be interpreted with caution due to the preliminary nature of the study, they highlight the potential contribution of clinician’s OT in facilitation the therapeutic process in acute settings, and call for further investigation in larger, controlled trials.